1991
DOI: 10.1002/ajh.2830380312
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinous transformation of marrow in a case of acute myelogenous leukemia post‐chemotherapy

Abstract: Gelatinous transformation of marrow in a patient with acute myelogenous leukemia was reported. This case was at variance with other reported cases of gelatinous transformation of marrow in that a) it was associated with a primary bone marrow disease and b) there was no fat atrophy and the patient was not cachectic. The fact that it occurred abruptly post-chemotherapy suggested that marrow hypoplasia induced by chemotherapy could be the cause of this lesion in this particular situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…A variant of GMT without fat cell atrophy has also been described in acute myeloblastic leukemia after chemotherapy [9]. This pattern was also seen in a case of CML described by Hong et al [7] and possibly our patient too has this variant.…”
supporting
confidence: 50%
“…A variant of GMT without fat cell atrophy has also been described in acute myeloblastic leukemia after chemotherapy [9]. This pattern was also seen in a case of CML described by Hong et al [7] and possibly our patient too has this variant.…”
supporting
confidence: 50%
“…In addition to the classical syndrome, a variant of GMT characterized by adipocyte hyperplasia has been described in postchemotherapy leukemia and myeloma patients and in patients with myelofibrosis treated with cytoreductive drugs [9,10,11,12]. Clinically, unlike the classical form, chemotherapy-associated GMT was acute in onset, transient and not associated with cachexia [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in leukemic patients the malignant cells may produce hyaluronic acid as a transient event, culminating by filling up of marrow space by either hematopoietic precursors or the leukemic cells themselves [9, 10]. In these cases GMT might not have any prognostic significance and survival of the patients is dependent solely on the nature of the malignant process [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GMT is not a specific disease of the bone marrow, but it is instead associated with generalized severe illnesses (3). There are several reports of the associations between GMT and anorexia nervosa (4)(5)(6), malignancy (7,8) and infectious diseases such as tuberculosis (9), human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS) (10,11). However, there have so far been few reports describing the associations between GMT and metabolic abnormalities.We herein present the first reported case of an association between GMT and a primary insufficiency of the adrenal and thyroid glands.…”
Section: Introductionmentioning
confidence: 99%